Creative Freedom behind Bars: A Dive in the Art of Prisons from Piaui State, in Brazil (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Valdsom Braga narrates his experience as Art Director at prisons in Piauí State, Brazil, from January 19 of 2016 to January 19, 2019. He identifies art as a tool for social change and highlights that society should be trained to accept, and not to exclude, people deprived from liberty. Valdsom also compares the situation in prisons to the situation in the state schools from Piauí, where he is currently the Art Director of a project focused on defending life and fighting suicide widely.
Keywords: Political theater; Art and Activism; Theater in Prisons